2018
DOI: 10.5152/eurjrheum.2017.16088
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic pain in pregnant Turkish women with lumbopelvic pain and its impact on health-related quality of life

Abstract: The present study is the first to demonstrate that neuropathic pain is associated with pregnancy-related LPP and strongly correlated with functional impairment and deterioration in the HRQoL. A better understanding of neuropathic pain mechanisms in pregnancy-related LPP will help us find more effective treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In addition, a numerical rating scale (0 being no pain, and 10 being worst pain imaginable) is used to measure the labor pain intensity. The SF-MPQ-2 has shown good correlation with the standard form and has been validated in obstetric population where pain evaluation is often restricted by time distress during the labor process; 15,18 ii) pain catastrophizing scale (PCS), a validated self-reported questionnaire to evaluate negative thought processes that one may have with https://doi.org/10.2147/JPR.S331703…”
Section: Recruitmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a numerical rating scale (0 being no pain, and 10 being worst pain imaginable) is used to measure the labor pain intensity. The SF-MPQ-2 has shown good correlation with the standard form and has been validated in obstetric population where pain evaluation is often restricted by time distress during the labor process; 15,18 ii) pain catastrophizing scale (PCS), a validated self-reported questionnaire to evaluate negative thought processes that one may have with https://doi.org/10.2147/JPR.S331703…”
Section: Recruitmentmentioning
confidence: 99%
“…13 Neuropathic pain is "pain caused by a primary lesion or dysfunction in the nervous system", often described as pain of "burning, electric shock-like, prickling, or itching sensations or numbness". 14,15 A recent development of short-form McGill pain questionnaire-2 (SF-MPQ-2) includes the qualities of both neuropathic and non-neuropathic pain and has since proven usefulness in patients with acute pain and cesarean delivery. [16][17][18] However, the evidence for its use in assessing labor pain should be further explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 Neuropathic pain has been reported during the peripartum and postpartum periods, and could reduce functional status and health-related quality of life in pregnant women. 12 Interestingly, both depression and anxiety are well-known co-morbidities with neuropathic pain, especially in chronic pain patients. A recent animal study showed that neuropathic pain state may promote adaptations in gene expressions responsible for anxiety and depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Consequently, this condition leads to problems-related pregnancy, including low back pain, pelvic girdle pain, sleep disturbance, and mental health problem and during pregnancy. [9][10][11][12][13][14][15] Around 50-70% of pregnant women reported low back pain (LBP) during pregnancy [2][3][4][5] and it was found that their problems start more often in the second trimester (43,23%) 6 and third trimester of pregnancy. 1 LBP during pregnancy is assumed as a reasonable condition worldwide.…”
Section: Introductionmentioning
confidence: 99%